Making the Grade during Pandemic: Early-stage and Late-stage Provisional Institutions. (October 2021) - Kinney, Alexander B.; Rowland, Nicholas J.
This is an article that draws on the institutional work literature about provisional institutions. To date, nearly every U.S. sector has been impacted by COVID-19. To sustain their core missions, highly institutionalized organizations such as universities have had to rethink foundational structures and policies. Using a historical ethnographic approach to investigate records from faculty senate deliberations at "Rural State University" (RSU), the authors examine the implementation of a temporary grading policy to supplement traditional, qualitative grades spring 2020 during the outbreak. The authors find that RSU implemented a temporary, supplemental grading policy as a provisional institution to momentarily supersede traditional grading as a means to—as soon as possible—return to it. This finding contrasts with the common understanding that provisional institutions operate primarily as a temporary solution to a social problem that leads to more stable and enduring, ostensibly nonprovisional institutions. The temporary grading policy, the authors argue, constitutes a "late-stage" provisional institution and, with this new lens, subsequently characterize the more commonplace understanding of provisional institutions as "early-stage." This contribution has theoretical implications for studies of institutions and empirical implications for research on shared governance and disruption in higher education.